O MARANHÃO EM HAICAI: Canto de Sabiá, de Benedita Azevedo - SANTOS, Marco Aurélio Goulart dos (2024)
This research aimed to investigate, as a general objective, taking the resonance of haiku as a method and starting from a historical-cultural approach, if the author, Benedita Azevedo, elaborates the poetic form of her writing under the influence of traditional haiku - when dealing with elements specific to Maranhão culture and consequently Brazilian culture, identifying the significant and relevant traits established in the realm of creation and intertextuality in the final product of her poetry. And, as specific objectives: 1) to understand the aesthetics of literary creation from the West and the East, with the intention of making a kind of intercultural and literary approximation and distancing of the two worlds, specifically of poetry; 2) to express how haiku reached Brazil and how this poetic form was received in Brazilian soil, and also to trace the importance of Haiku Guilds today (specifically Sabiá and Águas de Março) for the dissemination of this poetic form that gains more space in Brazilian Literature every day; 3) to analyze the poems of the work Canto de Sabiá (2006) through the peculiarities of classical haiku, without rhymes, without titles, and with Brazilian kigo, referring to each season and discussing the conception of the reading subject, based on the pretense idea that reading haiku is a negotiation of meaning, and in this vein we resort to the Theory of Aesthetic Effect, by Iser (1996; 1999). The critical-reflective perspective of knowledge construction is one in which there is space for questioning and reflection on the ordering of things, which enables the construction of meanings and significances. Therefore, we are guided by the guiding question: Does Benedita Azevedo re-signify such poetic form within her own culture? To this end, the characteristics of the seasons in the Brazilian scenario were identified through Goga and Oda's kigology (1996), as a possible answer to our problem, in an analysis of the poems in the writing Canto de Sabiá. The methodological procedure employed in this work, to achieve the proposed objectives, consisted of bibliographic review: articles, books, magazines, and websites related to the proposed theme; thus, it is linked to the qualitative research paradigm, and it consisted of analyzing 20 haikus from the aforementioned work, divided into the four seasons of the year: spring, summer, autumn, and winter, and in regular themes, such as experience, fauna, flora, time, and region. Thus, we situate our discussion in several authors who deal with this theme: about the Western and Eastern world focused on poetry, we anchor ourselves in Miner (1996), Paz (2012; 2015). Regarding the theorization of haiku, we rely on Cunha (2019); Franchetti (2012); Iura (2021); Lira (2018; 2020), among others. Regarding the negotiation of meaning between author and reader in haiku, we rely on Iser (1996; 1999); Goga (2008); Lira (2006) and others. The results pointed to the historiography of some haikuists from Maranhão in confluence with the analysis of the work Canto de Sabiá. What was verified, in the context of Benedita Azevedo's work, is that she was enchanted by Japanese literature, haiku, precisely because it is poetry that values simplicity and unveils an imagistic universe. In the development of the dissertation writing, we sought to clarify the understanding of what haiku is and the lack of theory about it in Maranhão, establishing a contextualized work of literary text, developed from the mediation of history and the wok Canto de Sabiá. Therefore, we conclude that the elements of nature used by the haijin, according to the poems we analyzed, point to the existence of cultural hybridizations both in the nature of the poem, which no longer belongs to just one culture, as well as in the cultural identity of the author in question, which shifts from a set of literary genres already crystallized in her culture to produce, according to her experiences, a poetic form distinct from those she had at her disposal, often returning to her place of origin through these elements of nature, the kigo. It is also worth mentioning the emphasis given to the reading subject as an active participant in the process of creating meanings for the literary text, for the haiku.